Materialy po izucheniiu giliatskago iazyka i fol'k-lora, Chast 1. Epos (poemy i skazaniia, pervaia polovina) . - Shternberg, Lev I͡Akovlevich, 1861-1927 (S.-Peterburg, Tip. Imperatorskoǐ akademii nauk, 1908)
No more published? Mode of access: Internet.